Pengaruh Brand Awareness, Kualitas Produk Dan Word Of Mouth Terhadap Keputusan Pembelian Kartu Perdana XL Di Kota Bogor - Muhammad Rafli; Sujana Sujana (LPPM IBI Kesatuan, 2022)
This study aims to analyze the effect of Brand Awareness, Product Quality, and Word of Mouth on XL Prime Card Purchase Decisions in Bogor City. The purposes of this study are (1) to determine and analyze the effect of brand awareness on purchasing decisions of xl starter packs. (2) To find out and analyze the effect of product quality on purchasing decisions of xl starter packs. (3) To find out and analyze the effect of word of mouth on the purchasing decision of the xl starter pack. The number of samples used in this study were 200 respondents, taken from those who used XL starter packs and those who had used XL starter packs. The tool used to collect data is a questionnaire with results, which were analyzed using Structural Equation Modeling (SEM) Moment Structure Analysis (AMOS) version 24.0. It is used to test three research hypotheses. The results showed that the value of the Goodness of Fit criteria was Chi-Square = 176.026; Significance Probability = 0.046 ; RMSEA = 0.032 ; GFI = 0.918 ; AGFI = 0.872 ; CMIIN/DF = 1,206 ; TLI = 0.984 and CFI = 0.987. The results of this study also show that (1) Brand Awareness (X1) has a positive and significant effect on Purchase Decisions (Y) with a critical ratio value (C.R.) of 2,021 greater than 1.96 with a probability value of 0.043 which is smaller than 0, 05 ; (2) Product Quality (X2) has a positive and significant effect on Purchase Decisions (Y) with a critical ratio value (C.R.) of 2,417 which is greater than 1.96 with a probability value of 0.016 which is less than 0.05; (3) Word of Mouth (X3) has a positive and significant effect on Purchase Decision (Y) with a critical ratio value (C.R.) of 5.426 which is greater than 1.96 with a probability value of 0.000 which is smaller than 0.05. So it can be concluded in the results of this study indicate that there is a positive impact of the variable Brand Awareness on Purchase Decisions, Product Quality on Purchase Decisions and Word of Mouth on Purchase Decisions. Keyword : Brand Awareness, Product Quality, Word of Mouth, Sem